PENGARUH LINGKUNGAN KERJA, PENGEMBANGAN KARIR DAN PROMOSI JABATAN TERHADAP KEPUASAN KERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA BINJAI - Yoan W ahyudi; Anton A.P. Sinaga; Erwin Pardede (JURNAL PROINTEGRITA, 2021)
In this study, the factors studied are the work environment, career development and promotion. This study aims at finding the effect of the work environment, career development and job promotion partially as well as simultaneously on employee job satisfaction at the Binjai Pratama Tax Office. The population of this research is 108 employees. In determining the sample used the Slovin formula, obtained as many as 52 people. The data collection techniques used are questionnaires, interviews and documentation studies while the data analysis technique used is the classical assumption test, multiple regression, t test, F test and the coefficient of determination. The results of this study indicate that the work environment shows a significant influence on employee job satisfaction at the Binjai Pratama Tax Office, where the better the work environment variables, the better the employee job satisfaction. Career development shows a significant influence on employee job satisfaction, where the better the career development variable, the better the employee job satisfaction. Job promotion has a significant effect on employee job satisfaction, where the better the promotion, the better the employee job satisfaction. Simultaneously there is a significant influence on work environment variables, career development, and job promotion on employee job satisfaction.